Políticas ambientais, mudanças sociais e econômicas na Reserva Extrativista Marinha de Cururupu - Leite, Luiza Moraes (2022)
The struggle for the awareness of nature becomes more difficult every day when we we are faced with a scenario o f immense predatory capitalism, where what matters most is the accumulation o f wealth and material goods, which make us feel or let us have the feeling that we are satisfied and that we are eager to get and win further. It is through this interest that the alert for environmental issues was linked and environmental laws and policies were created. Starting with the Extractive Reserve (RE SEX), its year o f creation and its functionality focus in particular on the RESEX of Cururupu. Extractive Reserves are areas used by traditional populations, whose livelihoods are based on extractivism, subsistence agriculture and small animal breeding. It should also be noted that its basic objectives are to maintain the culture of local populations, protect their livelihoods and ensure sustainable use (BRASIL, 2000), working with IBGE data in sectors 26. where the communities of Retiro. Iguará and Mirinzal are located, and in sector 28, where the community of Bate Vento is located. In this conception, the objective o f this work was to analyze through Brazilian environmental policies the socioeconomic changes that occurred in the RESEX o f Cururupu, comparing through the 2000 Census that precedes its creation and the 2010 Census that is after its creation and that bring the understanding of situations that are analyzed through the so-called variables, so that a conclusion can be reached on the situation found in the communities. To understand how the work of Community-Based Tourism works, thus carried out by them due to the inclusion of residents within their communities Interviews were carried out with ICMBio technicians who work within the studied area and also in managing bodies at the headquarters of Cururupu, with the purpose to understand the entire process of creating the RESEX and also to have knowledge o f updated data within the objectives worked. The results obtained through the IBGE database and the interviews showed a socioeconomic fluctuation, in which some variables in the year 2000 were more positive in relation to 2010, but others followed in the opposite way. with better results in the Census o f 2010 compared to 2000